Disposition and metabolism of [14C] Sacubitril/Valsartan (formerly LCZ696) an angiotensin receptor neprilysin inhibitor, in healthy subjects. (1st November 2016) - Flarakos, Jimmy; Du, Yancy; Bedman, Timothy; Al-Share, Qusai; Jordaan, Pierre; Chandra, Priya; Albrecht, Diego; Wang, Lai; Gu, Helen; Einolf, Heidi J.; Huskey, Su-Er; Mangold, James B.
Abstract: 1. Sacubitril/valsartan (LCZ696) is an angiotensin receptor neprilysin inhibitor (ARNI) providing simultaneous inhibition of neprilysin (neutral endopeptidase 24.11; NEP) and blockade of the angiotensin II type-1 (AT1) receptor. 2. Following oral administration, [ 14 C]LCZ696 delivers systemic exposure to valsartan and AHU377 (sacubitril), which is rapidly metabolized to LBQ657 (M1), the biologically active neprilysin inhibitor. Peak sacubitril plasma concentrations were reached within 0.5–1 h. The mean terminal half-lives of sacubitril, LBQ657 and valsartan were ∼1.3, ∼12 and ∼21 h, respectively. 3. Renal excretion was the dominant route of elimination of radioactivity in human. Urine accounted for 51.7–67.8% and feces for 36.9 to 48.3 % of the total radioactivity. The majority of the drug was excreted as the active metabolite LBQ657 in urine and feces, total accounting for ∼85.5% of the total dose. 4. Based upon in vitro studies, the potential for LCZ696 to inhibit or induce cytochrome P450 (CYP) enzymes and cause CYP-mediated drug interactions clinically was found to be low.